SISTEM INFORMASI ADMINISTRASI PENJUALAN SEPEDA MOTOR BERBASIS WEB MENGGUNAKAN UML, PHP DAN MYSQL: WEB-BASED MOTORCYCLE SALES ADMINISTRATIVE INFORMATION SYSTEM USING UML, PHP AND MYSQL - Ghea Paulina Suri (YCMM, 2020)
Motorcycle Sales Company that uses a computerized system in all its activities, one of which is PT Capella Dinamik Nusantara which is a motorcycle sales company. Management needs to improve the performance of the service system to stakeholders because the current sales information system does not meet satisfaction standards, both in terms of time, quality and in terms of reports, because reports are a support for management in decision making, but in the marketing department it has not been computerized based on the web but still uses Microsoft Excel, this results in the marketing department often having difficulty in making decisions to determine motorcycle sales targets and results, which can result in management being less precise in making decisions based on existing sales data. Therefore it is necessary to create a system, in developing a sales information system in the marketing department that is appropriate and accurate to handle problems at PT Capella Dinamik Nusantara, especially in the marketing section such as requests for the number of motorcycles sold, costomer data information, motorcycle stock according to type and the latest types of models, sales chart table can be seen. Therefore it is necessary to build a data main to manage all this information. By designing the system using the UML (Unified Modeling Language) method, as well as in the process of making the system using the PHP programming language with a database built using SQL, the system will be easy to implement. With the new system, it is hoped that it can help interested marketing departments to obtain sales information.